Chemical constituents of the stems of Neolitsea kedahensis Gamble - Jani, Nor Akmalazura; Mohd Sirat, Hasnah; Ahmad, Farediah; Abed, Salam Ahmed; Aminudin, Nurul Iman (Elsevier Ltd, 2018)
Two new β-carboline alkaloids, daibucarbolines D (1) and E (2) and one new sesquiterpene dilactone, pseudovillosine (3), together with five known compounds, taraxerone, taraxerol, pseudoneoliacine, daibucarboline A and linderaggrine A were isolated from the stems of Neolitsea kedahensis (Lauraceae). The structures were confirmed through extensive spectroscopic analysis, while the relative configuration of compound (3) was determined by a single crystal X-ray diffraction.